Systems synthesis of discrete Walsh-similarly sequention functions of eighth degree - Белецкий, Анатолий Яковлевич; Навроцкий, Денис Александрович (Ukrainian Scientific Journal of Information Security, 2016)
This paper proposes an algorithm for constructing in the space of discrete images (0.1) - Sequention functions that make up the complete system of orthogonal equidistant symmetrical features of the eighth order. Discrete sequention functions are formed by the replacement of a piecewise constant values of +1 or -1 in the time domain (of the original space), respectively, numerical val-ues 0 and 1 in the image space. For Walsh-like attribute such (0,1)-sequention function in which the number of ones and zeros in each half of the interval determination is not necessarily the same, as is the case in the images of the Walsh functions (except for the function, the left half which is filled with zeros, and the right-units). The method of directed enumeration each of the 30 groups form a complete equidistant sequent unfold as a group of the classical Walsh functions of order eight, 28 symmetric systems sequention functions.